Systematic Review on Effect of Tai Chi Regarding to Glucolipid Metabolism and Life Quality of Type 2 Diabetes Mellitus - Yongjin LIU; Bo DU; Bowei HUANG; Liuqing YANG; Suping HUANG (康复学报)
Objective:To systematically review the effect of Tai Chi exercise on glucolipid metabolism and life quality of type 2 diabetes mellitus (T2DM).Methods:We searched PubMed, FMRS, EMbase, The Cochrane Library, CNKI, WanFang and VIP databases to collect randomized controlled trials (RCTs) published before February 2017 about Tai Chi exercise on glucolipid metabolism and life quality of T2DM. Two reviewers independently screened literature, extracted data and assessed the risk of bias of included studies. Meta-analysis was performed through RevMan 5.3 software.Results:A total of ten RCTs were included. The results of Metaanalysis demonstrated that Tai Chi exercise had positive effect on the levels of FBG [SMD=-0.39, 95%CI (-0.54, -0.24), P<0.01], HbA1c [WMD=-0.59, 95%CI (-0.73, -0.44), P<0.01], TG [SMD=-0.52, 95%CI (-0.85, -0.19), P<0.01], HDL-C [SMD=0.31, 95%CI (0.14, 0.47), P<0.01], LDL-C [WMD=-0.32, 95%CI (-0.59, -0.05), P<0.05] and most items of quality of life; while there was no statistically significant on the levels of TC [SMD=-0.24, 95%CI (-0.58, 0.10), P>0.05], physical function and body pain.Conclusion:Tai Chi exercise is effective to improve the levels of glucolipid metabolism and life quality of T2DM. Tai Chi exercise is recommendable as an essential measure in diabetes management.